Comparative performance of two whole‐genome capture methodologies on ancient DNA Illumina libraries. Issue 6 (31st March 2015) - Ávila‐Arcos, María C.; Sandoval‐Velasco, Marcela; Schroeder, Hannes; Carpenter, Meredith L.; Malaspinas, Anna‐Sapfo; Wales, Nathan; Peñaloza, Fernando; Bustamante, Carlos D.; Gilbert, M. Thomas P.; Bunce, Michael
Summary Application of whole‐genome capture (WGC) methods to ancient DNA (aDNA) promises to increase efficiency of ancient genome sequencing. We compared the performance of two recent WGC methods in enriching human aDNA within Illumina libraries built using both double‐stranded and single‐stranded build protocols. Although both methods effectively enriched aDNA, we observed consistent differences between the methods, providing the opportunity to further explore parameters influencing WGC experiments. Our results suggest bait length has a potential influence on library enrichment. Moreover, we show WGC biases against shorter molecules that are enriched in single‐stranded libraries preparation protocols. Lastly, we document the effect of WGC on features including clonality, GC composition and repetitive DNA content. Our findings provide insights relevant to those planning WGC on aDNA and suggest future tests and optimization to improve WGC efficiency.